2013
DOI: 10.3233/ifs-120673
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy multi-criteria approach to point-factor method for job evaluation

Abstract: Job evaluation is the process of systematically determining a relative internal value of a job in an organization. The most widespread method applied in job evaluation process is the point-factor method. In this method, for determining the worth of a job, a set of compensable factors are identified. In this study, a fuzzy multi-criteria approach is developed for job evaluation. In the first stage, factors are weighted by using a Fuzzy Analytic Hierarchy Process (F-AHP) method. Afterwards, the obtained weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The most important disadvantage of these models is that they ignore the definitions of the levels while obtaining the level weights. Another disadvantage of these methods in the difficulty to define constraints as many as the number of jobs and variables as many as the number of factors [14]. Das and Garcia-Diaz [5] develop a computerized statistical method based on the central distribution and correlation measures.…”
Section: Job Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important disadvantage of these models is that they ignore the definitions of the levels while obtaining the level weights. Another disadvantage of these methods in the difficulty to define constraints as many as the number of jobs and variables as many as the number of factors [14]. Das and Garcia-Diaz [5] develop a computerized statistical method based on the central distribution and correlation measures.…”
Section: Job Evaluationmentioning
confidence: 99%
“…They showed that the results of their analysis were close to the choices of the decision makers. Kutlu et al [14] and Kutlu et al [19] proposed a multi-criteria fuzzy approach for the job evaluation problem.…”
Section: Job Evaluationmentioning
confidence: 99%
“…Job evaluation has been commonly used to establish a foundation for developing a fair wage structure and sustaining internal equity [ 2 ]. Specifically, job evaluation refers to a method for systematically determining the relative internal value of different jobs in an organization [ 2 – 4 ]. It can be used to design a fair payroll structure by comparing the relative similarities and differences in the content and the value of jobs.…”
Section: Introductionmentioning
confidence: 99%
“…The point-factor approach evaluates each position’s value through a set of compensable factors. These factors refer to the specific characteristics of the positions that contribute to the fulfilment of an organization’s strategy and objectives, and they are typically categorized as skills, responsibilities, effort and working conditions [ 4 , 8 , 9 ]. In this method, there is a scale defined by a number of levels for each of the factors, and each level is associated with a certain point value.…”
Section: Introductionmentioning
confidence: 99%
“…İş değerleme, işlerin analiz edilerek tanımlanması ve birtakım kriterlere dayalı olarak işlerin zorluk ve önem ağırlıklarının şeffaf ve sistematik bir şekilde belirlenmesi şeklinde tanımlanmaktadır (Aydın, 1983). İş değerleme ile ilgili çalışmalarsa, ağırlıklı olarak, işlerin en etkili hangi teknikle daha doğru değerlendirilebileceğinin belirlenmesine yönelik olarak yürütülmektedir (Kutlu, Ekmekçioğlu ve Kahraman, 2013;Leonard, 2011;Raju, 1998;Nistor, 2012;Sun ve Luo, 2013).…”
Section: Introductionunclassified